AGO Algorithms for the Treatment of Breast Cancer: Update 2021 - Schneeweiss, Andreas; Fasching, Peter A.; Fehm, Tanja; Gerber, Bernd; Jackisch, Christian; Loibl, Sibylle; Schmidt, Marcus; Stickeler, Elmar; Wöckel, Achim; Janni, Wolfgang; Müller, Volkmar; on behalf of the AGO Kommission Mamma (Geburtshilfe und Frauenheilkunde, 2021)
Therapy options shown in the algorithms are based on the current AGO recommendations, but cannot represent all evidence-based treatment options, since prior therapies, performance status, comorbidities, patient preference, etc. must be taken into account for the actual treatment choice. In individual cases, other evidence-based treatment options may also be appropriate and justified. Regardless of approval status, the algorithms only take into account drugs that were available in Germany at the time the algorithm was last updated. Here we present the 2021 update of AGO treatment algorithms for early and metastatic breast cancer, which are intended to intensify structured treatment decision by providing reproducible and evidence-based treatment paths and may be helpful for a broad treatment landscape.
Keywords: therapy algorithms; evidence-based treatment; breast cancer guidelines